CONTRIBUTION OF PPKN TEACHERS TO POLITICAL EDUCATION THROUGH PPKN INSTRUCTION AT STATE MIDDLE SCHOOL 6 TERNATE - Noe, Wahyudin; Adnan, Mardiana; Misrina, Misrina; Wicaksono, Muhammad Arif; Djohra, M. Rifaldi A. (Jambura Journal Civic Education, 2025)
Engagement in political activities reflects a high degree of citizencomprehension and awareness in achieving democracy.Consequently, political education within PPKn lessons in schools iscrucial for enhancing students' understanding and politicalconsciousness as young citizens, who are anticipated to activelyengage in politics in the future. This research seeks to explore therole of educators in delivering political education through PPKninstruction at SMP Negeri 6 Ternate. This investigation is adescriptive qualitative study. The findings reveal that: 1) Teachersplay a role in political education within PPKn lessons by: a)encouraging student participation by allowing them to voice theiropinions, b) instilling democratic values and independence, and c)fostering democratic attitudes among students; 2) Factors affectingteachers in delivering political education include teacher quality andschool support, such as learning facilities and a conducive sociallearning environment; and 3) Student feedback on the politicaleducation provided through PPKn lessons is very positive, as it helpsstudents become more confident and courageous in expressing theirviews, enhances critical thinking and civic awareness, and boostsstudent interaction and collaboration.